First-ever community-level Anticipatory Action Simulation in Sri Lanka - Alahacoon, Niranga; Amarnath, Giriraj; Gnanatheepan, W. (International Water Management Institute, 2023)
Sri Lanka experiences distinct monsoon seasons, the Southwest and Northeast monsoons, contributing to the risk of flooding and landslides in different regions. The Nuwara Eliya district, facing elevated threats of landslides and floods, underscores the importance of proactive measures such as Anticipatory Action (AA). AA empowers communities by enabling precautionary measures, and a collaborative three-day simulation, involving World Vision Lanka, the International Water Management Institute (IWMI), and government partners, sought to enhance community resilience comprehensively. The simulation focused on holistic empowerment, resilience-building, coordination strengthening, and increased awareness. The AA simulation, spanning preparedness, readiness, and activation triggers, involved early warnings that activated AA protocols. Community engagement included awareness campaigns, evacuation planning, and resource pre-positioning. As rainfall intensified, readiness triggers prompted canal cleaning, slope stabilization, and household preparations. The active phase featured an evacuation alert efficiently communicated by Mr. Early Warning. Community members, supported by various stakeholders, were evacuated to safety centers, with special attention to vulnerable groups and diverse services ensuring their well-being. Feedback highlighted positive responses to early warnings and potential practice impact. However, confidence levels varied regarding facing future disasters, and community satisfaction with services indicated room for improvement. Accessibility and support services for vulnerable groups emphasized the need for enhanced inclusivity in disaster preparedness. The simulation, a collaborative effort of key agencies, showcased a comprehensive approach, providing valuable insights for future initiatives.